Analisis Injeksi Daya Reaktif Untuk Memperbaiki Faktor Daya Pada Line Instalasi Listrik Gedung Workshop AK-Manufaktur Bantaeng - Hermansyah Hermansyah (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
This research is a case study, namely the electrical installation system for AK-Manufacturing Bantaeng fabrication workshops. This study aims to improve the value of cos φ (power factor) from 0.75 to 0.97 and to determine the capacity of the capacitor bank that will be installed on the electrical installation line of the AK-Manufacturing Bantaeng Fabrication Machine workshop building. The problem that occurs is the low value of cos φ (power factor) in the installed electrical system which causes the installed active power to be not maximal. For this reason, a capacitor bank with an adjusted capacity value is needed to provide reactive power injection so that the value of cos φ can be increased from 0.75 to 0.97. This study uses an analysis method to determine the value of reactive power to be injected into the electrical installation system. The results of this study indicate that the required reactive power injection capacity is 12 KVar or 12,000 Var. This value is sufficient to improve the power factor from 0.75 to 0.97. This means that the electrical installation system is more optimal.